Glomerular Hyperfiltration is a new marker of fibrosis severity in non-cirrhotic NAFLD. (March 2023) - Dalbeni, A.; Garbin, M.; Zoncapè, M.; Romeo, S.; Cattazzo, F.; Mantovani, A.; Cespiati, A.; Mantovani, A.; Fracanzani, A.L.; Tsochatzis, E.; Sacerdoti, D.; Lombardi, R.
Abstract : Background: Non-alcoholic fatty liver disease (NAFLD) represents a risk factor for development of cardiovascular disease and chronic kidney failure, early expressed by glomerular hyperfiltration (GH). GH shares the same cardiovascular and metabolic risk factors as NAFLD. Their association has already been evaluated in adults with metabolic syndrome. Despite that, association between GH and NAFLD fibrosis is not described in literature. Methods: 597 patients, with an age between 18 and 60 years old, from three centers (Verona, Milan and London) with non-cirrhotic NAFLD diagnosed by abdominal ultrasound, were enrolled. The degree of steatosis and stiffness were assessed by sonography and Fibroscan (echoSense), respectively. Glomerular filtration rate (GFR) was estimated using 2021CKD-EPI formula. Two different classes were defined: normal (<110 and >60 mL/min)(nGFR) and hyperfiltration (≥ 110 mL/min)(hGFR). Main anthropometric and biochemical indexes, medical history, current therapy and smoke habits were recorded. Results: Of the 597 (mean age 51.2±5.41, 64% male) enrolled patients, 541 had nGFR, 56 hGFR. The hGFR group was characterized by a younger age (47.2 ± 5.2 vs 51.6 ± 5.3, p<0.001), reduced use of beta blockers (2.9% vs 14.7% p=0.03), lower s-creatinine [61.0 (CI 52.5 – 67.0) vs 75.0 (CI 67.0 – 86.0), p<0.01]. Mean stiffness was 6.30 (CI 4.85–9.65) kPa in hGFR, compared to 5.90 (CI 4.50–8.00) kPa in nGFR (p=0.030) and grade 3 steatosis was more frequent in hGFR group (54.4% vs 36.4%, p=0.03). Using univariate and multivariate models with GFR as dependent variable, age, male sex and stiffness were independent variables (OR 0.8, 0.03, 5.78, respectively). The collinearity showed a strong link between hyperfiltration and stiffness (VIF=1). Conclusions: GH correlates with a worse degree of liver stiffness. Therefore, hGFR could be considered an early marker of liver fibrosis in non-cirrhotic NAFLD patients.